Prosocial Personality and Self-Harm Tendencies in Young Adults: The Mediating Role of Self-Compassion and Resilience - Qureshi, Nabia; Sana, Fatima; Latif, Areeba; Raza, Muhammad Ali Jawad; Awaisi, Zahra Bakhat (Dialogue Social Science Review (DSSR), 2025)
The main aim of the research study was to determine the mediating role of self-compassion and resilience between prosocial personalities and self-harm tendencies. The study included 300 university students ranging in age from 17 to 25 years (M =21.1, SD = 2). The measures included in the study were self-compassion scale, resilience scale, prosocial personality scale, and self-harm tendencies scales was used. The results highlighted that prosocial personality, self-compassion, resilience, and self-harm tendencies were significantly related to each other. Whereas, all the study variables predicted each other. Also, it was concluded that self-compassion and resilience partially mediated the relationship between prosocial personality and self-harm tendencies. The findings will help in future development of effective techniques and interventions employed in reducing self-harm tendencies. The limitations and future suggestions are given at the end of the study.